Health behaviors and life satisfaction among Polish classically trained singers: a cross-sectional study - Cezary Roman; Mateusz Cybulski; Anna Zalewska; Bożena Czarkowska-Pączek; Anna Marchewka; Krystyna Rożek-Piechura (Frontiers in Public Health, 2026)
Introduction Health behaviors and life satisfaction are important health-related outcomes in professional voice users, yet evidence among classically trained singers remains limited. This online cross-sectional study assessed health behaviors and life satisfaction among Polish classically trained singers and examined their associations with selected sociodemographic and occupational factors. Methods Data were collected from May to July 2024 among 241 adult Polish classically trained singers, including professional singers and vocal students (151 women and 90 men; age range, 20–73 years). Health behaviors were assessed using the Health Behavior Inventory (HBI), and life satisfaction was assessed using the Satisfaction With Life Scale (SWLS). Group differences were examined using the Mann–Whitney U and Kruskal–Wallis tests, associations using Spearman's rank correlation coefficient, and multivariable linear regression models were fitted for the SWLS and total HBI scores with adjustment for age, sex, and type of vocal work. The Holm procedure was applied to account for multiple comparisons. Results An average level of health behaviors was most common (42.7%), followed by low (32.4%) and high (24.9%) levels, and 55.2% of participants were classified in one of the satisfied-with-life categories. Life satisfaction was positively associated with the total HBI score (ρ = 0.508, 95% CI: 0.406–0.599; Holm-adjusted p < 0.001) and all four HBI domains (all adjusted p < 0.001), with the strongest association observed for positive mental attitude (ρ = 0.528, 95% CI: 0.429–0.616). After correction for multiple comparisons, women had higher scores than men for proper eating habits, health practices, and the total HBI score. In the multivariable analysis, sex was associated with the total HBI score, with women scoring 6.26 points higher than men after adjustment for age and type of vocal work (B = 6.257, 95% CI: 3.270–9.245; p < 0.001). No statistically significant adjusted associations with SWLS were observed for age, sex, or type of vocal work. Discussion Health behaviors were positively associated with life satisfaction in this sample of Polish classically trained singers. The findings provide baseline evidence on health behaviors and life satisfaction in this specific performing-arts population and may inform further health-promotion research; however, the cross-sectional design precludes conclusions regarding temporal or causal relationships.